PENGEMBANGAN LEMBAR KERJA PESERTA DIDIK MENGGUNAKAN SOFTWARE GEOGEBRA PADA MATERI TRANSFORMASI GEOMETRI - Mariyanti Elvi; Nur Asma Riani Siregar; Susanti Susanti (Alifmatika (Jurnal pendidikan dan pembelajaran Matematika), 2021)
Geometry is a mathematical science that studied points, lines, planes, spaces, and the relationships of them. One of the topic is geometric transformation. The Several research found that students hadn’t understood the concept of transformation, so that it needed a teaching material especially student’s worksheet. The research aimed to develop valid, practical and effective student’s worksheet with GeoGebra on the geometry transformation in junior high school. The research method was used R&D (Research and Development) using a modification of the 4-D model. The development model consists defined, designed and developed. The results of the research indicated that (1) this product was valid according to media experts and material experts, (2) it was practical, (3) effective to be used in mathematics learning, especially geometric transformation.